Whale in the sky - Siberell, Anne. (New York : Dutton, 1982)
Describes the Northwest Indian totem pole which shows how Thunderbird punished Whale for chasing Salmon and scaring Frog.
"A Unicorn book."
Keywords: Indians of North America -- Northwest Coast of North America; Totem poles; Indians of North America -- Northwest Coast of North America; Totem poles; Animals